2017
DOI: 10.1039/c6nr09951c
|View full text |Cite
|
Sign up to set email alerts
|

Grating-coupled surface plasmon resonance enhanced organic photovoltaic devices induced by Blu-ray disc recordable and Blu-ray disc grating structures

Abstract: In this work, we studied the performance enhancement of organic thin-film solar cells (OSCs) originating from the presence of diffraction gratings on the surface of the active layer. Two types of diffraction gratings, periodic gratings (Blu-ray disc recordable: BD-R) and quasi-random gratings (Blu-ray disc: BD), were employed as master templates for grating structures. The grating structures were introduced to the surfaces of poly(3-hexylthiophene) (P3HT):phenyl-C-butyric acid methyl ester (PCBM) films, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…The extracted PCE and J SC values are shown as a function of ODT content in Figure b. The values without ODT match commonly achieved PCE values for not fully optimized device architectures (e.g., no antireflection coating) . A gradual improvement in PCE with increasing ODT content is observed, which is mainly ascribed to the positive development of J SC .…”
Section: Resultsmentioning
confidence: 54%
“…The extracted PCE and J SC values are shown as a function of ODT content in Figure b. The values without ODT match commonly achieved PCE values for not fully optimized device architectures (e.g., no antireflection coating) . A gradual improvement in PCE with increasing ODT content is observed, which is mainly ascribed to the positive development of J SC .…”
Section: Resultsmentioning
confidence: 54%
“…A more recent example of this is the demonstration of Blu‐ray discs as a mold for imprinting. It was demonstrated that that higher enhancements are achieved with a bare, unrecorded disc, as compared to a recorded disc with quasi‐random structures …”
Section: Patterned Structures For Optical In‐couplingmentioning
confidence: 99%
“…It permits the control of the chemistry, patterning of large areas, and scalable production of patterned surfaces. Hence, to improve solar-cell performances, this NIL process has been recently employed for the formation of an irregular nanoscale-featured surface by using nanoporous anodic aluminum oxide (AAO) membrane filters 20 , the formation of ordered nano/microstructures by using a large-scale nanoporous Si mold and AAO templates 21,22 , and the formation of a grating structure by Blu-ray movie discs (BD) and Blu-ray disc-recordable (BD-R) 23,24 . The latter involves the plasmonic effect at the patterned metallic electrodes.…”
Section: Introductionmentioning
confidence: 99%